2018
DOI: 10.1038/s41563-018-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Electron delocalization and charge mobility as a function of reduction in a metal–organic framework

Abstract: Conductive metal-organic frameworks are an emerging class of three-dimensional architectures with degrees of modularity, synthetic flexibility and structural predictability that are unprecedented in other porous materials. However, engendering long-range charge delocalization and establishing synthetic strategies that are broadly applicable to the diverse range of structures encountered for this class of materials remain challenging. Here, we report the synthesis of K Fe(BDP) (0 ≤ x ≤ 2; BDP = 1,4-benzenedipyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
215
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(222 citation statements)
references
References 57 publications
5
215
1
1
Order By: Relevance
“…[1,2] Due to the diversity in composition/ structure,h igh surface area, and chemical/thermal stability, MOFs have been applied in many areas including gas separation/storage,s ensors,a nd catalysis. [3][4][5][6][7][8] Recently, MOFs have been rising as af ascinating family of electrocatalysts providing insight in both homogeneous and heterogeneous chemistry:t he well-defined structures and readily accessible active sites can be tuned at the molecular level to improve the catalytic performance and they also enable the MOFs to serve as model systems for the fundamental understanding of catalytic mechanisms.R ecently,v arious MOFs,s uch as [Cu 2 (OH)(bpy) 2 (btc) 3 ], [Fe 2 (Fe(tcpp))Cl], [Cu 3 (btc) 2 (H 2 O) 3 ], and [Co(mim) 2 ], have been explored as oxygen reduction reaction (ORR) electrocatalysts. [2,[9][10][11][12] However,g reat challenges still remain for conventional MOFs including electrical insulators and the blockage of metal centers by organic ligands;this leads to inferior activity (halfwave potential E 1/2 < 0.8 Vv s. RHE) and dramatically limits their broader applications in electrocatalysis.P yrolysis of MOFs to provide metal-and heteroatom-doped porous carbons has been widely demonstrated to improve the catalytic activity.…”
mentioning
confidence: 99%
“…[1,2] Due to the diversity in composition/ structure,h igh surface area, and chemical/thermal stability, MOFs have been applied in many areas including gas separation/storage,s ensors,a nd catalysis. [3][4][5][6][7][8] Recently, MOFs have been rising as af ascinating family of electrocatalysts providing insight in both homogeneous and heterogeneous chemistry:t he well-defined structures and readily accessible active sites can be tuned at the molecular level to improve the catalytic performance and they also enable the MOFs to serve as model systems for the fundamental understanding of catalytic mechanisms.R ecently,v arious MOFs,s uch as [Cu 2 (OH)(bpy) 2 (btc) 3 ], [Fe 2 (Fe(tcpp))Cl], [Cu 3 (btc) 2 (H 2 O) 3 ], and [Co(mim) 2 ], have been explored as oxygen reduction reaction (ORR) electrocatalysts. [2,[9][10][11][12] However,g reat challenges still remain for conventional MOFs including electrical insulators and the blockage of metal centers by organic ligands;this leads to inferior activity (halfwave potential E 1/2 < 0.8 Vv s. RHE) and dramatically limits their broader applications in electrocatalysis.P yrolysis of MOFs to provide metal-and heteroatom-doped porous carbons has been widely demonstrated to improve the catalytic activity.…”
mentioning
confidence: 99%
“…For example, K x Fe 2 (BDP) 3 is composed of mixed-valence metal node and BDP 2À (BDP 2À = 1,4-benzenedipyrazolate) Linkers. [56] A reduction process forces the obtained crystal to capture some K + ions into the frameworks. After incorporation of the K + ions, this compound showed remarkable enhancement in electronic conductivity by a four-order magnitude.…”
Section: Mixed-valence Metal Nodesmentioning
confidence: 99%
“…This strategy of using metal ion doping to change the internal energy level of the semiconductor to improve its photocatalytic performance is also useful in super capacitor. Aubrey et al [158] found that through the introduction of K + , the energy band delocalization of semiconductors could be realized, and the conductivity and mobility of MOFs were greatly improved, to a status comparable to these of organic polymers. The researchers believed that this excellent performance is mainly due to the introduction of K + and the resultant production of intervalence charge-transfer (IVÀ CT), which greatly enhanced charge delocalization.…”
Section: Valence-level Regulation Mechanismmentioning
confidence: 99%
“…The double-headed arrow indicates the (001) direction aligned with the long axis of the crystal. Reproduced with permission from Ref [158]…”
mentioning
confidence: 99%